Investigation into the accuracy of subjective load parameters in comparison to analytical load measurements in NCAA Division I women`s volleyball - Pierce, K.; Phillips, J.; Loprinzi, P.; Jessee, M.; Andre, T.; Nelson, H.; Valliant, M. (Scientific Journal of Sport and Performance, 2023)
Monitoring athletes` workload has become common practice in sports and differs depending on the sport`s physical demands. Within volleyball, an inertial measurement unit can be utilized to track the number of jumps performed by players. However, other methods of measuring jump frequency are needed for teams without access to this equipment. The purpose of this study was to determine if volleyball athletes can accurately predict the number of jumps performed after training and matches when given a perceptual scale and if player position, session rating of perceived exertion (sRPE), and perceived sets played affected the players` accuracy. Less than half of the team`s jump count estimations (23.2%) were within 25 of the actual number of jumps and over half of the players` responses (58%) were within 50 of the measured number of jumps. A generalized estimating equation (GEE) with a binary response was used to investigate the impact of position, sRPE, and sets played. Position was the only variable to have a significant impact on jump count accuracy. Based on these results, a perceptual scale could be useful in better understanding players` jump counts following training, but number of jumps allotted to each jump range and position could impact accuracy.